An explorative study into Faith healing as an African belief system and its influence on the diagnosis and treatment of mental illness in the Eastern Cape province, South Africa - Tsotsi, Liso (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
The present study specifically focussed on Faith healing as an indigenous healing system and its influence on the diagnosis and treatment of mental illnesses in the Eastern Cape province of South Africa. The study aimed to provide a descriptive overview of Faith healers' perspectives on the diagnosis and treatment of mental illnesses in the Eastern Cape, as well as to compare conclusions reached with other categories of indigenous healers. The inter-category comparisons on a broader level allowed for a further comparative discourse with the mainstream western medical psychiatric view of mental illness. Therefore, the scope of this study does not include in-depth analyses of findings, but rather the generation of themes for comparative discussions. While there exists vast literature on the diagnostic and treatment perspectives of the other two categories of indigenous healing systems (traditional healers and herbalists), a limited number of studies have been focussed on Faith healing as an indigenous mode of healing. The present study attempted to address this gap in the literature in an effort to promote future collaborative work across all viewpoints, in the management of mental illnesses. This study, grounded in qualitative research, utilized thematic analysis as its theoretical framework. Non probability judgmental sampling was used to secure self-identifying Faith healers, where conclusions from them were drawn from data collected, using in depth semi-structured interviews and observation. The main findings of the study indicated that Faith healers' perspectives on the diagnosis and treatment of mental illnesses are based mainly on indigenous cultural theories. Furthermore, that collaboration with other viewpoints is hampered by animosity, feelings of distrust and the fear of appearing inferior.
Keywords: Traditional medicine -- South Africa -- Eastern Cape; Spiritual healing -- South Africa -- Eastern Cape; Ethnopsychology -- South Africa -- Eastern Cape; Mental illness -- Treatment -- South Africa -- Eastern Cape; Mental illness -- Alternative treatment -- South Africa -- Eastern Cape